OPTIMALISASI UNIT PELAKSANA TEKNIS LATIHAN KERJA (UPT-LK) DALAM MENCIPTAKAN SUMBER DAYA MANUSIA YANG TRAMPIL DAN KREATIF WILAYAH I KOTA PEKANBARU, PROVINSI RIAU - Rizki Muhammad Rizdu; Zaili Rusli SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The Technical Implementation Unit for Job Training (UPT-LK) is an organization under the supervision of the Pekanbaru City Manpower and Transmigration Agency (DISNAKERTRANS). The establishment of the Technical Work Training Unit is an optimization step to create skilled and creative human resources in Region I of  Pekanbaru City, Riau Province. With the presence of optimization it is hoped that all activities carried out can run effectively and efficiently. The purpose of this study is to determine how the optimization activities have been carried out and to find out what are the inhibiting factors of optimization Unit Executor Technical Work Training (UPT-LK) Region I Pekanbaru City, Riau Province. This research uses qualitative methods using interview, documentation, and observation techniques. The results of this study indicate that: first, optimization carried out by Unit Implementing Technical Training Work Region I Pekanbaru City, Riau Province in this case, the creation of skilled and creative human resources has not been maximized. Second, the inhibiting factors are the lack of facilities and infrastructure, lack of financial assistance from the government, and lack of teaching staff..Keywords: Optimization, Organization, Management